ACADEMIC REVIEW OF BIO-OIL PURIFICATION TECHNOLOGY FROM PLASTIC AND BIOMASS WASTE PYROLYSIS IN RECENT RESEARCH - Asfihani; Wahyudi Sahputra; M. Yusuf (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This academic review comprehensively analyzes the development of bio-oil refining technology from the pyrolysis of mixed plastic and biomass waste, focusing on its characteristics, technical challenges, and application prospects in Indonesia. Mixed bio-oil has a complex composition influenced by radical interactions during pyrolysis, resulting in high-value hydrocarbon fractions but still containing oxygenated compounds that reduce fuel stability and quality. This study examines the effectiveness of major refining methods, including hydrodeoxygenation (HDO), catalytic cracking, and integrated co-pyrolysis, and assesses the performance of latest generation catalysts such as NiMo/Al₂O₃ and ZSM-5, which demonstrate significant selectivity and reaction stability. The analysis also identifies obstacles to industrial-scale implementation, such as catalyst deactivation, high hydrogen requirements, feedstock variability, and high operating costs. In the Indonesian context, the potential for application of this technology is significant due to the abundance of biomass and plastic waste, coupled with renewable energy policies that support diversification of energy sources. This review emphasizes the need for research integration, process optimization, infrastructure capacity building, and collaboration between government, industry, and academia to accelerate the development of efficient, economical, and sustainable bio-oil refining technology.